Neonates and Young Infants With COVID-19 Presented With Sepsis-Like Syndrome: A Retrospective Case Controlled Study - Hassan, Manasik; Khalil, Ahmed; Magboul, Samar; Alomari, Ohood; Abdalla, Tasneim; Alsliman, Hafez; Alhothi, Abdulla; Al Maslamani, Eman; AlAmri, Mohammed; Soliman, Ashraf (Frontiers in Pediatrics, 2021)
Objective: We aimed to describe the presentations and biochemical characteristics of sepsis-like syndrome (SLS) in infants aged <2 months who tested positive for SARS-CoV-2-in comparison to those in the same age group who were SARS-CoV-2-negative. Background: COVID-19 presents with a spectrum of manifestations, and children seem to have a favourable clinical course compared to other age groups. Limited data are available for symptomatic infants. Design: A controlled single-institution retrospective study on infants <2 months admitted with SLS between 1 April2020 and 1 July2020. Infants were divided into 2 groups: Group-1(n=41), infants with positive nasal/oropharyngeal swab polymerase chain reaction (PCR) results for SARS-CoV-2; and Group-2(n=40), infants with negative PCR results for SARS-CoV-2(control group). Details between both groups were reviewed and analysed. Outcome: The clinical and laboratory data for SARS-CoV-2 -positive infants who presented with SLS may differ from those for infants with SLS who tested negative for SARS-CoV-2. Results: 105 infants admitted with clinical sepsis: 41 were COVID-19 positive, and 64 were negative. Fever was present in 90% of SARS-CoV-2-positive infants versus 80% of the negative group. SARS-CoV-2-positive infants had a higher incidence of nasal congestion and cough (39% and 29%, respectively) compared to the SARS-CoV-2-negative group (20% and 3%, respectively) (P<0.05). Poor feeding and hypoactivity occurred more frequently in the SARS-CoV-2-negative group (58%and45%, respectively) than in the SARS-CoV-2-positive group (22%and12%, respectively, P< 0.004). Sepsis workup including lumbar puncture was performed in67% and partial septic workup was performed in23% of the SARS-CoV-2-positive infants. Full sepsis workup was performed in92% of the SARS-CoV-2-negative group. Cerebrospinal fluid(CSF) cultures were negative in 26/27SARS-CoV-2-positive infants (an infant had Klebsiella meningitis). All the SARS-CoV-2-negative infants had negative CSF cultures. Blood culture was negative in both groups. Urine culture showed bacterial growth in 9 infants with SARS-CoV-2-negative sepsis. Conclusions: Our study showed that respiratory symptoms(cough and nasal congestion) were more prominent in the SARS-CoV-2-positive group, while poor feeding and hypoactivity were reported more frequently in the negative group. However, the clinical differentiation between COVID-19 disease and sepsis in such age groups is difficult. Therefore, screening young infants with SLS for SARS-CoV-2- is necessary during this pandemic.